Truncated lubricin glycans in osteoarthritis stimulate the synoviocyte secretion of VEGFA, IL-8, and MIP-1α: Interplay between O-linked glycosylation and inflammatory cytokines - Huang, Shan; Thomsson, Kristina A.; Jin, Chunsheng; Ryberg, Henrik; Das, Nabangshu; Struglics, André; Rolfson, Ola; Björkman, Lena I.; Eisler, Thomas; Schmidt, Tannin A.; Jay, Gregory D.; Krawetz, Roman; et al. (Frontiers in Molecular Biosciences, 2022)
The primary aim of the study was to identify inflammatory markers relevant for osteoarthritis (OA) related systemic (plasma) and local (synovial fluid, SF) inflammation. Following on from this we looked for inflammatory markers that coincided with the increased amount of O-linked Tn-antigen (GalNAcalpha1-Ser/Thr) glycan on SF lubricin. Inflammatory markers in plasma and SF in OA patients and controls were measured using a 44 multi-plex immunoassay. We found consistently 29 markers detected in both plasma and SF. The difference in their concentration and the low correlation when comparing SF and plasma, suggests an independent inflammatory environment in the two biofluids. Only plasma MCP-4 and TARC increased in our patient cohort compared to control plasma. To address the second task, we concluded that plasma markers were irrelevant for a direct connection with SF glycosylation. Hence, we correlated the SF-inflammatory marker concentrations with the level of altered glycosylation of SF-lubricin. We found that the level of SF-IL-8 and SF-MIP-1alpha and SF-VEGFA in OA patients displayed a positive correlation to the altered lubricin glycosylation. Furthermore, when exposing fibroblast like synoviocytes from both controls and OA patients to glycovariants of recombinant lubricin, the secretion of IL-8 and MIP-1alpha and VEGFA were elevated using lubricin with Tn-antigens, while lubricin with sialylated and non-sialylated T antigens had less or no measurable effect. These data suggest that truncated glycans of lubricin, as found in OA, promotes synovial pro-inflammatory cytokine production and exacerbates the local synovial inflammation.